The availability of child care and mothers' employment in West Germany - Michaela Kreyenfeld; Karsten Hank (Deutsches Institut für Wirtschaftsforschung (DIW), 1999)
There is a vast empirical literature investigating the effects of child care costs on female employment. Day care costs are usually treated as a reduction in female wages, which is supposed to negatively affect a woman's propensity to participate in the labor market. In this paper, we argue that due to peculiarities of the German day care regime, an analysis of the effects of child care on mothers' employment in Germany should rather focus on the availabililty than on the affordability of care. Our empirical findings cast doubt on the effectiveness of the current German day care regime with regard to enabling mothers to work in the labor market.
Keywords: 330; Frauenerwerbstätigkeit; Arbeitsangebot; Kinderbetreuung; Schätzung; Deutschland